Efek Problem Based Learning terhadap Keterampilan Berpikir Kritis dan Minat Belajar IPA Siswa - Nur'aini, Aisa; Ernawati, Tias; Listiyani, Laily Rochmawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2024)
The implementation of Problem Based Learning (PBL) in the classroom is able to condition students to the situation of linking concepts with problems in everyday life. This study aims to determine the effect of PBL on critical thinking skills and students' interest in learning science. The research design was pretest-posttest control group design with quasi-experiment type. The sample was obtained through simple random sampling. Data were collected using critical thinking skills test questions, learning interest questionnaire, and documentation. Data analysis through the analysis of normal curve criteria, N-Gain, and t test. The results showed that the posttest score of critical thinking skills of the experimental class was in the very high category, while the control class was high. The N-Gain score of the experimental class and control class was in the medium category. Learning interest of both classes in the high category. The t-test on the critical thinking skills variable and the learning interest variable obtained a sig value. 0,000 (< α). Thus, there is a significant difference in the experimental class against the control class. Based on the data, it is concluded that PBL has an effect on students' critical thinking skills and interest in learning science.